Strong Impact of Interviewers on Respondents' Political Choice: Evidence from Hungary. Issue 2 (May 2018) - Németh, Renáta; Luksander, Alexandra
Despite much literature on interviewer effects, limited attention has been paid to party preference surveys, although the effect is expectedly strong in this field. This article analyzes interviewer effects in a face-to-face political survey. Specifically, we are interested in whether the interviewer's own party preference has an effect on the respondent's party choice. We used cross-classified two-level logistic regression models with median odds ratio as effect size. We found four main results: (1) Place of residence significantly affects political preference, but interviewers do so to the same degree; (2) the size of these effects is comparable to those of demographic characteristics of the respondent; (3) interviewers' political preference has an effect and it does not disappear once controlled for obvious interviewer characteristics; and (4) the impact of political preference is such that respondents tend to have a preference similar to that of their interviewers.